The Effect of Total Quality Management (TQM) on Employee Performance With Employee Satisfaction As A Mediating Variable In Manufacturing Companies - Ilham, Nurul Ilham; Rahmiati, Rahmiati (Universitas Negeri Padang, 2024)
The purpose of this study was to determine the effect of Total Quality Management (TQM) on Employee Performance with Employee Satisfaction as a Mediating Variable in Manufacturing Companies. This type of research uses quantitative research. The population in this study were employees of manufacturing companies in Padang City totaling 530 people. The sampling technique used proportionate stratified random sampling totaling 147 people. Data collection using a questionnaire. The analysis method uses Partial Least Square using Smart PLS. The results showed that: The influence of information processing in this review shows that: (1) Leadership has a positive and significant influence on employee satisfaction. (2) Education and training have no significant effect on employee satisfaction. (3) Teamwork has no significant effect on employee satisfaction. (4) Employee relations have a positive and significant influence on employee satisfaction. (5) Employee satisfaction has a positive and significant influence on employee performance. (6) Leadership has no significant effect on employee performance. (7) Education and training has a positive and significant influence on employee performance. (8) Teamwork has no significant effect on employee satisfaction. (9) Employee relations have a positive and significant influence on employee performance.